1959
DOI: 10.1021/ja01520a076
|View full text |Cite
|
Sign up to set email alerts
|

A STEREOSPECIFIC SYNTHESIS OF dl-SHIKIMIC ACID1

Abstract: COMMUNICATIOKS TO THE EDITOR 2909 acid3 and the oxidized protein was partially hydrolyzed (12 N HC1, 105', 3 hours). The hydroly-(1) C 0 Overberger, R J Ehrig and D 'Tanner, Tms J O U K~ 11 76,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The most common method for synthesis of racemic SA was obtained by Diels Alder reaction with (1E, 3E)-1,4-diacetoxy-1,3-butadiene, and in this method acrylic acid was used as starting material for the SA synthesis with 15% yield [27,28]. Pinus sylvestris Summer, winter needles Bochkov et al [26] Other studies have also reported that SA was synthesized from (À)-quinic acid obtained from cinchona bark [29].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The most common method for synthesis of racemic SA was obtained by Diels Alder reaction with (1E, 3E)-1,4-diacetoxy-1,3-butadiene, and in this method acrylic acid was used as starting material for the SA synthesis with 15% yield [27,28]. Pinus sylvestris Summer, winter needles Bochkov et al [26] Other studies have also reported that SA was synthesized from (À)-quinic acid obtained from cinchona bark [29].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…The material from (16) was contaminated with (22), and also (24) which presumably arises from (26) as an impurity in the bromo-compound (16). Hydrogen fluoride catalysed isomerization of (20) gave, after deacetylation, Comparison of the n.m.r.…”
Section: 'Ozhmentioning
confidence: 99%
“…To a solution of 9 (0.260 g, 0.69 mmol) in dichloromethane (10 mL), was added 1,8-diazabicyclo [5,4,0.530 g,3.48 mmol). The reaction mixture was then stirred at room temperature for 6 h. After the reaction was complete, dichloromethane (20 mL) and dilute aqueous HCl solution (2 N, 25 mL) were added, and stirring was continued for 15 min.…”
Section: (à)-Methyl 345-o-triacetyl Shikimate 10mentioning
confidence: 99%
“…4 A series of methods over the last decades have been found to synthesize racemic or enantiomerically pure shikimic acid, and an excellent review has summarized these methods. 5 They can be briefly classified into four categories: (a) syntheses based on the Diels-Alder reaction; 3,4,6 (b) syntheses from benzene and its derivatives; 7 (c) syntheses from (À)-quinic acid; 8 and (d) syntheses from carbohydrates. 9 Carbohydrates that are naturally abundant and inherently rich in chiral centers have played an important role in the syntheses of natural products.…”
Section: Introductionmentioning
confidence: 99%